Deteksi Kebocoran Gas menggunakan Sensor MQ2 berbasis WeMos D1 Mini - Syuja Rifka Khairyansyah; Kalika Khaldan Nurshofa; Della Saskia Amelia; Aulivia Widya Putti; Muhammad Taufiq Hidayatullah Syari; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This research develops an IoT-based gas detection system using an MQ2 sensor, WeMos D1 Mini, and the Blynk application to monitor hazardous gases such as LPG. The MQ2 sensor detects gases, the WEMOS D1 Mini transmits data via Wi-Fi, and Blynk enables real-time monitoring and notifications if gas concentrations reach a specified threshold. Results indicate that this system is effective, accessible, and suitable for enhancing safety in environments prone to gas leaks.